Prevención de Fusarium oxysporum raza 1, en el cultivo de banano variedad Gros Michel, utilizando Trichoderma spp. en la zona de Naranjal - Ecuador - CHICA CONTRERAS GRISELDA DAYANA (2025)
In the present investigation, the prevention of Fusarium oxysporum race 1 was evaluated in the Gros Michel variety with applications of Trichoderma spp. in the Naranjal area. A Completely Randomized Block Design was applied in three replications. Tukey's test at 5 % of significance was performed to determine the difference between the following treatments: T1: Biohealth, T2: Dinamics, T3: Control. The following variables were evaluated: Percentage of affected plants with symptoms of Fusarium oxysporum race 1, bunch age, number of bunches, number of hands, bunch weight (kg), finger length (inches), last hand calibration, second hand calibration, ratio and economic analysis. The results indicate that there were symptomless plants at 15 days, 30 days and 45 days in the treatments studied. Symptoms of the FOCRT1 disease were present from 129 days, with a higher percentage of affectation in T3 (12.13 %), while T1 (10 %) presented a lower percentage of affectation. At 213 days, there was a higher percentage of affectation in T3 (23.33 %), while T1 (16.67 %) presented a lower percentage of affectation. As at 224 days, there was a higher percentage of damage in T3 (36%), while T1 (26.67%) had a lower percentage of damage. It was determined that the highest number of hands per bunch was reported in treatment T1 (9.40) being statistically superior to the other treatments, while the lowest number of hands per bunch was presented in treatment T3 (8). The greatest finger length was reported in treatment T2 (10.97 inches) being statistically superior to the other treatments, while the least finger length was presented in treatment T1 (9 inches). The highest calibration of the last hand of the bunch was reported in treatment T1 (42.53) being statistically superior to the other treatments, while the lowest calibration of the last hand of the bunch was presented in treatment T3 (40.67). The highest calibration of the second hand of the bunch was reported in treatment T3 (46.40) being statistically superior to the other treatments, while the lowest calibration of the second hand of the bunch was presented in treatment T1 (45.07). Based on the economic analysis carried out in the best treatment (T1), it was found that the production costs of the different cultural labors in one hectare of production had a value of $ 6097.44.